Qui construit le paysage bruxellois ? Le cas de Tour et Taxis - Sophie Hubaut (Projets de Paysage)
The landscape is increasingly being used as an object and a tool for conducting contemporary urban projects. In such a context, power struggles, tensions, and coalitions between actors contribute to defining the landscape. The article seeks to shed light on this political dimension of the landscape through the case of the re-use of the Tour & Taxis industrial site in Brussels. The article examines the way in which the notion of landscape is addressed in the field : who uses it, and how it is used, what does it cover on such occasions ? And what concrete effects does it have on the urban project, on its development and on the resulting uses ? The study makes it possible to identify the different notions of the landscape that have emerged, developed, circulated, and been confronted to one another, thus composing the different layers in the site resulting from the ways it has been used during the last thirty years as the actors appeared and the key questions concerning heritage, social, economic, and environmental issues evolved.